Preoperative plasma fibrinogen combined with the platelet-to-lymphocyte ratio (F-PLR) serves as a prognostic indicator in patients with non-small cell lung cancer - Zhao, Hongzhen; Zhang, Xiaopeng; Ren, Dahu; Liu, Shicheng; Wang, Yuedong; Wu, Wenbo; Zhang, Kun; Niu, Yajing; Duan, Guochen (Frontiers in Oncology, 2025)
BackgroundThe aim of this study was to explore the prognostic significance of the combined plasma fibrinogen level and platelet-to-lymphocyte ratio (F-PLR) score in patients who had undergone radical surgery for non-small cell lung cancer (NSCLC).MethodsIn this study, we retrospectively reviewed the medical records of 214 patients who underwent radical resection for lung cancer. The optimal cut-off values for fibrinogen and the platelet - lymphocyte ratio (PLR) were determined by applying the receiver operating characteristic (ROC) curve and the Youden index. Based on these cut-off values, the patients were categorized into three groups: patients with elevated fibrinogen and PLR were assigned a score of 2; those with either elevated fibrinogen or PLR were assigned a score of 1; and those with neither elevation were assigned a score of 0. The Kaplan-Meier method was utilized to plot the survival curves, and differences among the curves were compared using the log - rank test. Univariate and multivariate analyses were carried out using the Cox proportional hazards model.ResultsIn this study, the optimal cutoff values were 3.90 for fibrinogen and 213.2 for the PLR. Cox’s multifactorial analysis revealed that the implementation of adjuvant therapy after surgery(P<0.001), pathological stage(PStage=IIIA/I=0.041), and F-PLR(PF-PLR=1/0 = 0.006、PF-PLR=2/0 = 0.004)were independent prognostic factors influencing patient survival. Additionally, F-PLR was significantly correlated with the overall survival of NSCLC patients after surgery.ConclusionsThe F-PLR score exhibits a significant association with the prognosis of NSCLC patients and can serve as a biomarker for predicting the prognosis of patients following NSCLC surgery.